Psychological well-being: impact of workplace violence and demographic variables on employees of ministry of physical planning and urban development, Ibadan, Oyo State (2016)
The study investigated the influence of demographic factors and work place violence on psychological well-being among employees of ministry of physical planning and urban development, Ibadan , Oyo State. A structured questionnaire was adopted for data collection which was administered on two hundred employees. Data was analysed using descriptive and inferential statistics. Five hypotheses were stated and tested. Result showed there was a significant influence of workplace violence on psychological well-being [t(-15.418;df=199, p<.05).There was a significant influence of academic qualification on psychological well-being (F(2,198)=6.305; p<.05). age had significant influence on psychological well-being [t(-2.509;df=199, p<.05)]The mean observation however shows that older employees score higher (X=55.06) on psychological well-being than their counterparts (X=51.63). There was also a significant influence of years of experience on psychological well-being {t(-2.039;df=199, p<.05)}. Furthermore, the mean observations shows that respondents with high experience scored higher (X=55.19) on psychological well-being that their counterparts with lower experience (X=52.31). it was recommended that, future study can include a larger and more broader-based sample. It would be appropriate to conduct quantitative and qualitative studies with a larger and more heterogeneous sample